2022
DOI: 10.1111/pedi.13324
|View full text |Cite
|
Sign up to set email alerts
|

Caries experience and gingival health in children and adolescents with type 1 diabetes mellitus—A cross‐sectional study

Abstract: Aim To investigate the oral health of children and adolescents with type 1 diabetes (T1D) and its associations with diabetes‐related and lifestyle factors. Design Cross‐sectional study at a large tertiary hospital pediatric diabetes clinic. Oral examination determined dental caries experience and gingival health. Secondary outcome measures included salivary characteristics, oral hygiene and dietary practices, and diabetes‐related factors. Results Eighty children and adolescents with T1D participated; mean (SD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…This approves the opinion of some authors, who note that the oral hygiene indices did not have significant differences between patients with type 1 DM and the control group [2,3,8]. However, it disproves the opinion of other authors, who found that the value of oral hygiene indices in patients with type 1 DM was much higher compared to healthy patients [16,17,20]. The last statement can be confirmed by comparing groups 1 and 4, and 2 and 4, where the difference was significant (p<0.05).…”
supporting
confidence: 79%
See 1 more Smart Citation
“…This approves the opinion of some authors, who note that the oral hygiene indices did not have significant differences between patients with type 1 DM and the control group [2,3,8]. However, it disproves the opinion of other authors, who found that the value of oral hygiene indices in patients with type 1 DM was much higher compared to healthy patients [16,17,20]. The last statement can be confirmed by comparing groups 1 and 4, and 2 and 4, where the difference was significant (p<0.05).…”
supporting
confidence: 79%
“…Periodontitis and gingivitis are two kinds of periodontal diseases, known as complications in patients with DM and other systemic diseases [1,[10][11][12][13][14][15]. Special attention is paid to the condition of periodontium at an early age among patients with type 1 DM [16][17][18][19][20].…”
mentioning
confidence: 99%
“…Lacking of timely treatment, dental caries in children and adolescents can result in the development of an abscess or the death of a tooth [ 3 ]. Dental caries also affects general health in children and adolescents, and is associated with a number of diseases such as hypertension and type 1 diabetes [ 4 , 5 ]. Therefore, it is essential to explore the risk factors in dental caries to improve and prevent dental caries in a young age.…”
Section: Introductionmentioning
confidence: 99%